2016
DOI: 10.1159/000450567
|View full text |Cite
|
Sign up to set email alerts
|

Global Overexpression of ET-1 Decreases Blood Pressure - A Systematic Review and Meta-Analysis of ET-1 Transgenic Mice

Abstract: Background/Aims: ET-1 has independent effects on blood pressure regulation in vivo, it is involved in tubular water and salt excretion, promotes constriction of smooth muscle cells, modulates sympathetic nerve activity, and activates the liberation of nitric oxide. To determine the net effect of these partially counteracting mechanisms on blood pressure, a systematic meta-analysis was performed. Methods: Based on the principles of Cochrane systematic reviews, we searched in major literature databases - MEDLINE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The data was analyzed by the Review Manager Version 5.0 (Rev-Man 5.0) software as recently described [18]. The reliable test for overall effect was set as P <0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The data was analyzed by the Review Manager Version 5.0 (Rev-Man 5.0) software as recently described [18]. The reliable test for overall effect was set as P <0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses were conducted by Review Manager Version 5.0 (Rev-Man 5.0) software, devised by Co-chrane Collaboration as described earlier [11]. Heterogeneity was assessed by P value and I 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This meta-analysis provides robust evidence that global ET-1 overexpression in mice lowers blood pressure in an age-dependent manner. Older ET-1+/+ mice had even a somewhat more pronounced reduction of blood pressure as compared to younger ET-1 transgenic mice when comparing these mice to their age-matched controls [11]. Given this findings in transgenic endothelin rodent models, the aim of the current study therefore was to perform a systematic review and meta-analysis of all published studies on ET-1 plasma concentrations in human patients with hypertension published so far.…”
Section: Introductionmentioning
confidence: 99%
“…We recently performed a meta-analysis addressing this topic. This meta-analysis provides robust evidence that systemic ET-1 overexpression in mice lowers blood pressure in an age-dependent manner [11]. A subsequent meta-analysis -on the other hand -revealed that ET-1 plasma concentrations are elevated in humans with essential hypertension [12].…”
Section: Introductionmentioning
confidence: 71%
“…The meta-analysis was conducted according to principles and methods that we recently published [11,12,20,21].…”
Section: Methodsmentioning
confidence: 99%